Ticks and Associated Pathogens From Rescued Wild Animals in Rainforest Fragments of Northeastern Brazil - Fonseca, Maísa Santos; Bahiense, Thiago Campanharo; Silva, Aretha Alves Borges; Onofrio, Valeria Castilho; Barral, Thiago Doria; Souza, Barbara Maria Paraná; Lira-da-Silva, Rejane Maria; Biondi, Ilka; Meyer, Roberto; Portela, Ricardo Wagner (Frontiers in Veterinary Science, 2020)
The Ixodidae family comprises ticks that are hematophagous ectoparasites and are considered vectors of several hemoparasites from the Anaplasmataceae family and the genus Hepatozoon, Babesia and Rickettsia. These ectoparasites parasitize domestic and wild animals belonging to several vertebrate groups. Ticks are highly adapted to different biomes and thus possess a wide geographical distribution. In the Brazilian state of Bahia, localized in the Northeast region, there are large rainforest fragments. Studies have rarely been carried out on ticks, and their hemoparasites, that parasitize wild animals in this region. Thus, this study aimed to identify the tick species parasitizing wild animals rescued in rainforest fragments of Bahia and investigate the presence of hemoparasites in tick tissues. During a two-year period, 241 ticks were collected from 42 wild mammalians, reptiles, and amphibians. These ectoparasites were taxonomically classified according to their morphological characteristics. The ticks identified belonged to six different species from the Ixodidae family: Amblyomma varium, Amblyomma rotundatum, Amblyomma dissimile, Amblyomma nodosum, Ixodes loricatus and Rhipicephalus sanguineus. For the first time, an A. rotundatum parasitizing the Mesoclemmys tuberculata turtle was described. PCR assays using DNA extracted from salivary glands or midgut of the ticks were performed to detect specific DNA fragments of hemoparasites from the genus Rickettsia, Ehrlichia, Babesia, Hepatozoon and from the Anaplasmataceae family. The results showed positive detection of the Rickettsia genus (7.9%), Anaplasmataceae family (15.8%), and Hepatozoon genus (15.8%). Specific DNA from the Ehrlichia and Babesia genera were not detected in these samples. Specific DNA from members of the Anaplasmataceae family was detected in A. varium for the first time. The present work showed that amphibians, reptiles, and mammals from Bahia´s Atlantic Forest are parasitized by different tick species, and that these ectoparasites present pathogens in their tissues that impact both humans and animals due to their zoonotic potential.